The Effect Of Live Streaming And Brand Awareness On Purchasing Decisions Of Glad2Glow Products On Tiktok E-Commerce - Hili Puspita Sari; Ade Tiara Yulinda; Merta Kusuma (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Consumer purchasing decisions on social media–based e-commerce platforms are influenced by various factors, including live streaming and brand awareness. This study aims to analyze the effect of live streaming and brand awareness on purchasing decisions of Glad2Glow skincare products on TikTok e-commerce among consumers in Bengkulu City. This research employs a quantitative method with a survey approach. The population of this study consists of consumers in Bengkulu City who have purchased Glad2Glow products through TikTok live streaming. The research sample comprises 130 respondents selected using an accidental sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis. The results indicate that live streaming has a positive and significant effect on purchasing decisions, meaning that more effective live streaming increases consumers’ likelihood of making purchases. Brand awareness also has a positive and significant effect on purchasing decisions, indicating that higher brand awareness enhances consumer trust and confidence in choosing products. Furthermore, live streaming and brand awareness simultaneously have a positive and significant effect on purchasing decisions of Glad2Glow products on TikTok e-commerce. Therefore, Glad2Glow is recommended to continuously optimize its live streaming strategies and strengthen brand awareness to improve consumer purchasing decisions.